Чёрный принц: в поисках утраченного / Сарада Бёрд - Бёрд Сарада (Издательские решения, 2021)
Экземпляры: АБ (20221026) / Инвентарный номер: 70089 / Цена: 250.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Б 11 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6